A sigma factor that modifies the circadian expression of a subset of genes in cyanobacteria. - Tsinoremas, N F (1996)
We isolated mutants affected in the circadian expression of the psbAI gene in Synechococcus sp. strain PCC 7942 using a strategy that tags the genomic locus responsible for the mutant phenotype. The search identified one short period (22 h) mutant (M2) and two low amplitude mutants, one of which showed apparent arhythmia (M11) and one that was still clearly rhythmic (M16). We characterized the disrupted locus of the low amplitude but still rhythmic mutant (M16) as the rpoD2 gene, a member of a gene family that encodes sigma70-like transcription factors in Synechococcus. We also inactivated rpoD2 in a number of reporter strains and showed that the circadian expression of some genes is not modified by the loss of this sigma factor. Therefore, we conclude that rpoD2 is a component of an output pathway of the biological clock that affects the circadian expression of a subset of genes in Synechococcus. This work demonstrates a direct link between a transcription factor and the manifestation of circadian gene expression.